Hubungan Matematika Bisnis dan Matematika Ekonomi - Muhammad Surya Ananta; Ariantje Dimpudus (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research is a literature study on the relationship between business mathematics and economic mathematics, both in terms of concepts and applications. With an in-depth understanding of business mathematics, it is hoped that readers can appreciate the importance of applying mathematics in business decision-making and apply a data-driven scientific approach in their endeavors. Business mathematics is a very important science in modern management, helping companies to make better decisions, improve operational performance, and achieve goals in a fast-changing business environment